Potentiostatic curves of Fe, Ni and Co in the passivity and transpassivity regions in fused LiNo3-NaNO3-KNO3 eutectic - Podestá, José J. (1977)
The potentiostatic current of Fe, Co and Ni in molten LiNo3-NaNO3-KNO3 eutectic is studied in both the passive and transpassive regions. The processes are interpreted as the initial formation of an oxide film and as metal dissolution through the film. The various concurrent rate processes imply a change of the actual electrode area due to a localized metal corrosion. The latter depends both on the metal surface and the magnitude of the potential perturbation.